Economic costs of invasive alien species in the Mediterranean basin - Kourantidou, Melina (2021)
Invasive alien species (IAS) negatively impact the environment and undermine human well-being, often resulting in considerable economic costs. The Mediterranean basin is a culturally, socially and economically diverse region, harbouring many IAS that threaten economic and societal integrity in multiple ways. This paper is the first attempt to collectively quantify the reported economic costs of IAS in the Mediterranean basin, across a range of taxonomic, temporal and spatial descriptors. We identify correlates of costs from invasion damages and management expenditures among key socioeconomic variables, and determine network structures that link countries and invasive taxonomic groups. The total reported invasion costs in the Mediterranean basin amounted to $27.3 billion, or $3.6 billion when only realised costs were considered, and were found to have occurred over the last three decades. Our understanding of costs of invasions in the Mediterranean was largely limited to a few, primarily western European countries and to terrestrial ecosystems, despite the known presence of numerous high-impact aquatic invasive taxa. The vast majority of costs were attributed to damages or losses from invasions ($25.2 billion) and were mostly driven by France, Spain and to a lesser extent Italy and Libya, with significantly fewer costs attributed to management expenditure ($1.7 billion). Overall, invasion costs increased through time, with average annual costs between 1990 and 2017 estimated at $975.5 million. The lack of information from a large proportion of Mediterranean countries, reflected in the spatial and taxonomic connectivity analysis and the relationship of costs with socioeconomic variables, highlights the limits of the available data and the research effort needed to improve a collective understanding of the different facets of the costs of biological invasions. Our analysis of the reported costs associated with invasions in the Mediterranean sheds light on key knowledge gaps and provides a baseline for a Mediterranean-centric approach towards building policies and designing coordinated responses. In turn, these could help reach socially desirable outcomes and efficient use of resources invested in invasive species research and management.